I survived : the great molasses flood, 1919 - Tarshis, Lauren (Tarshis, Lauren. I survived, 2019)
"It's been four years since Carmen and Papa moved from Italy to Boston. Life here is exciting, but not always easy. And then there's the massive metal tank that rises up over their crowded North End neighborhood. The ugly tank, filled with sticky brown molasses, has always leaked. But nobody imagined that it could one day explode apart, sending a tsunami of molasses into the streets. Caught in the flood, Carmen must fight for her life, the life that she and Papa built together in America"--OCLC.